Overexpression of TSG101 causes the development of adenosquamous mammary carcinoma - Rayane Dennaoui; Patrick D. Rädler; Madison N. Wicker; Kerry Vistisen; Rosa‑Maria Ferraiuolo; Aleata A. Triplett; Hridaya Shrestha; Tessa A. Liner; Karoline C. Manthey; Hallgeir Rui; Robert D. Cardiff; Teresa M. Gunn; et al. (Breast Cancer Research)
Abstract Background The mammalian Tumor Susceptibility Gene 101 (TSG101) encodes a protein with diverse functions that control the proliferation and survival of cells, but its role in malignant transformation and cancer development has remained enigmatic. Methods To study the pro-tumorigenic functions of TSG101, we developed a bi-transgenic mouse model that expresses exogenous TSG101 along with a luciferase reporter in a ligand-controlled manner in the mammary gland epithelium. We performed a comprehensive histopathologic, biochemical, and molecular characterization of ductal hyperplasia and mammary tumors. Unsupervised hierarchical clustering based on 1,723 intrinsic genes of ten TSG101-overexpressing cancers alongside 251 tissue samples representing 31 reference mammary tumor models and normal mammary glands was conducted. Results Females overexpressing TSG101 develop ductal hyperplasia, adenomyoepitheliomas, and palpable adenosquamous carcinomas at an average latency of approximately ten months. These metaplastic mammary tumors are comprised of transforming basal and luminal epithelial cells. Using a GFP reporter strain to monitor the transgene activation at the single-cell level, we determined that the epithelial heterogeneity within transforming ducts and ensuing carcinomas originated from the luminal epithelium. At the molecular level, TSG101-induced mammary tumors are triple-negative and exhibit gene expression signatures of Wnt and inflammatory cytokine signaling, which are key regulators of epithelial cell fate. The ligand-controlled downregulation of exogenous TSG101 in established carcinomas led to tumor regression. We demonstrated that the TSG101-mediated activation of PI3K/AKT signaling, as well as upregulation of Cyclin D1 and MDM2, are dependent on the perpetual expression of the TSG101 oncoprotein. Conclusions The collective findings of this study provide in vivo evidence that TSG101 possesses pro-tumorigenic properties that extend to cancer progression and maintenance, suggesting that this protein could be a rational molecular target to prevent and treat a subset of mammary tumors.